Pelatihan Manajemen Green Marketing dan Peningkatan Kualitas Kemasan Produk UMKM Kabupaten Bogor - Hasanudin Hasanudin; Nurhasan Nurhasan; Rizky Muyasar; Bayu Satrio; Acip Sucipto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The Turmeric and Asem Herbal Home Industry is a pioneering MSME by housewives in RW.007 Cikeas Udik, Bogor Regency, and still faces several obstacles, including the still simple equipment used in production, the packaging used is still simple and in its marketing activities it has not implemented green economy-based marketing (green marketing). The purpose of this community service is to increase the productivity and marketing of the turmeric and asem herbal MSME, encouraging MSME actors to increase business productivity, creativity, innovation and entrepreneurial spirit in order to develop their business. The method of implementing the community service is the presentation of training materials that begins with a pre-test followed by a lecture on the material by the community service team and a question and answer discussion, closing with a post-test to determine the final abilities of the training participants. The results of this activity can increase the productivity and marketing of MSMEs turmeric and tamarind herbal medicine, encouraging MSMEs to increase business productivity, creativity, innovation and entrepreneurial spirit in order to develop their businesses. The output targets to be achieved The output targets to be achieved are improving management skills, improving the ability to design marketing strategies, publishing articles in reputable journals, IPR, posters and audio-visual works. In this activity, the Community Service Team distributed technology grants to partners from the Ministry of Education and Science and Technology through LLDIKTI 4 in the form of a spice or flour grinding machine. It is hoped that this program can increase the productivity, creativity, innovation and enthusiasm of MSME entrepreneurs and subsequently there will be several times of mentoring from the PKM team to ensure the sustainability of this activity.